PE NGARUH KOMPETENSI TERHADAP KINERJA PIMPINAN (STUDI KASUS PADA PT. DRILINCO DI PT. CHEVRON PACIFIC INDONESIA SUMATERA) - Togap Simangunsong; Sri Indarti; Zulfadil Zulfadil (Jurnal Ekonomi, 2014)
The purpose of this research is to analyze the effect of Communication Competency, Self Management Competency, and Technical Competency toward Leaders Performance of PT. Drilinco, partially and simultaneously. For that purpose, the research is conducted by taking sample of 84 leaders of PT. Drilinco. The analysis model using the multiple regression technique. For the hypothesis test is using the statistical test such as t test, determination test (R²) and F test.The result shows simultaneously that Communication Competency and Self Management Competency are effecting Leaders Performance of PT. Drilinco significantly. But on contrary, Technical Competency is not effecting Leaders Performance of PT. Drilinco significantly. Partially test on each variables’ effects are Communication Competency (17,7%)and Self Management variable (27,3%), this means Self Management variable is the most dominant variable effecting on Leaders Performance of PT. Drilinco, meanwhile Technical Competency variable is not effecting Leaders Performance of PT. Drilinco significantly. PT. Drilinco must keep trying to upgrade leaders’ Technical Competency by giving continuous training and development, also giving extra attention on increasing the level of Communication Competency and Self Management Competency simultaneously to upgrade Leaders Performance.